IN VITRO ANTIMICROBIAL ACTIVITY OF SOME ESSENTIAL OILS AGAINST BACTERIAL PATHOGENS CAUSING SKIN DISEASES IN VAPOR PHASE - PATTANAPANIT, PURIT; MITHONGLANG, SUNISA; MITHONGLANG, SUNITA; TECHAOEI, SURACHAI (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this study was to evaluate the antimicrobial activity of volatile oils from aromatic plants against pathogenic bacteria. Methods: Thai aromatic plants such as Pogostemon cablin (Blanco) Benth (Patchouli oil), Cymbopogon nardus Rendle (Citronella grass oil), Pelargonium roseum (Geranium oil), Syzygium aromaticum (L.) Merrill and Perry (clove oil), Cinnamomum spp.(cinnamon oil), and Cymbopogon citratus (DC.) Stapf. (lemongrass oil) were selected. Essential oils were obtained by water distillation and were stored at 4°C until use. Five human pathogenic bacteria were obtained from Thai traditional Medicine College, Rajamangala University of Technology, Staphylococcus epidermidis, Escherichia coli, Staphylococcus aureus, methicillin-resistant S. aureus (MRSA), and Pseudomonas aeruginosa. The antibacterial activity of volatile oils was determined by disc-diffusion assay. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of each essential oil were determined. Results: Our study showed that 10% of essential oil from Cinnamomum spp. was the most potential against S. aureus, MRSA, and E. coli when assayed by disc-diffusion method with inhibition zones ranging from 37.66±0.57 to 45.33±1.15 mm and from 29.33±0.57 to 36.00±1.00 for lemongrass oil with MIC and MBC of 1.25%. Conclusion: From this study, it can be concluded that some essential oils have potential antibacterial activity. The present investigation provides support to the antibacterial properties of essential oils and will be applied to health-care product as aroma antibacterial products.